Leitura na escola e na vida: a leitura-fruição como uma possibilidade na formação do leitor literário - Zottesso, Dulcinéia Fávaro (2020)
Reading is one of the axes of Portuguese language teaching. Among the types of reading, there is the one classified as reading-fruition (Geraldi, 2011), whose goal is to encourage reading by the teacher so that the student improves his reading in terms of quantity and quality, especially from the literary text, his ability to displace and change the meanings of the texts you already know, towards a better understanding of books, people and life (LAJOLO, 2006). Such research echoed from the observation that students were not in the habit of reading literary texts. Therefore, we seek to understand what would be the appropriate and pertinent activities to encourage the reading-enjoyment of the literary text for a class of 9th grade of elementary school in the city of Toledo - PR. The pedagogical practice was developed in the form of a teaching project, entitled “Reading at school and in life: the literary text in focus for the 9th year” and developed with students in the second half of 2019, during 32 classes. It was sought in pedagogical practice to emphasize the reading of diverse literary texts and to propose playful and differentiated activities, aiming to develop reading-fruition activities, considering the interest the participation of the students, as well as the concrete conditions of the classroom and the school. Methodologically, the research follows the assumptions of Applied Linguistics, a qualitative and interpretative type, of an ethnographic nature, with an emphasis on action research and with the field diary as an instrument for recording classes. Each class worked had its own records of the development of the activities proposed and carried out, following the analysis and results of what was discussed with the students. As a theoretical basis are Geraldi's teaching reading proposals (1997 and 2011), the reading problems presented by Leffa (1996), the concept of reading as an interaction practice exposed by Koch (2002), Santos (2011) and perspectives of reading and mediation by Petit (2009), among others. As a result of the application of pedagogical practice, it was realized that between what was planned and carried out, some adaptations were necessary, which is predictable in the teaching work. It was identified that the students' involvement was gradually greater in each of the classes, that the planning combined with the playful activities practiced in the classroom and other school environments proved the increase of the students' interest in the participation in the literary reading classes and provided greater capacity of reading by students in relation to the knowledge of different literary texts and the school's own collection. And finally, it was found that research and practice are part of a single process, in improving the teaching role in the training of the teacher-researcher.